Cytomegalovirus Retinitis in Immunocompetent Patients: Case Reports and Literature Review. (August 2013) - Radwan, Alaa; Metzinger, Jamie Lynne; Hinkle, David M.; Foster, C. Stephen
<x xml:space="preserve">Abstract</x> Purpose: The purpose of this study was to examine 2 cases of cytomegalovirus (CMV) retinitis, occuring in 2 immunocompentent adult patients. Methods: Case selection and literature review. Results: Both patients cited significantly decreased vision despite systemic, topical, and/or local corticosteroid use. Neither patient was using high-dose immunosuppressant therapy at the time of diagnostic testing. Both patients exhibited confirmed CMV infection via polymerase chain reaction DNA testing. Oral antivirals were employed and have stabilized both patients. Conclusion: The cases described herein serve to inform ophthalmologists of the urgent need to include CMV in their differential when encountering an immunocompetent adult with significant comorbidities or with a history of previous exposure. Proper treatment is heavily reliant on proper diagnosis.